2021
DOI: 10.3390/microorganisms9040850
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 IgG Antibodies Seroprevalence and Sera Neutralizing Activity in MEXICO: A National Cross-Sectional Study during 2020

Abstract: Until recently, the incidence of COVID-19 was primarily estimated using molecular diagnostic methods. However, the number of cases is vastly underreported using these methods. Seroprevalence studies estimate cumulative infection incidences and allow monitoring of transmission dynamics, and the presence of neutralizing antibodies in the population. In February 2020, the Mexican Social Security Institute began conducting anonymous unrelated sampling of residual sera from specimens across the country, excluding p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 25 publications
5
33
0
Order By: Relevance
“…This study was conducted later during the pandemic than other studies with similar and lower prevalence [ 8 – 10 , 33 ]; thus, the observed high prevalence may be explained by higher accumulation of cases. Second, our results are consistent with those of two large, national, seroepidemiological surveys, that observed that approximately one third of the general population had been exposed to SARS-CoV-2 by December 2020 [ 3 , 6 , 7 ]. This could be especially true in large urban centers such as Mexico City, which has contributed with a large proportion of the total national cases [ 1 , 3 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study was conducted later during the pandemic than other studies with similar and lower prevalence [ 8 – 10 , 33 ]; thus, the observed high prevalence may be explained by higher accumulation of cases. Second, our results are consistent with those of two large, national, seroepidemiological surveys, that observed that approximately one third of the general population had been exposed to SARS-CoV-2 by December 2020 [ 3 , 6 , 7 ]. This could be especially true in large urban centers such as Mexico City, which has contributed with a large proportion of the total national cases [ 1 , 3 ].…”
Section: Discussionsupporting
confidence: 90%
“…We enrolled participants during the second wave, which in Mexico City reached an estimated cumulative incidence of 434 cases per 100,000-person, reaching a maximum of 7371 cases per day (and over 20,000 cases per day at the country level) [ 1 , 5 ]. Preliminary and recently published results of nationally representative seroepidemiological surveys in Mexico estimated that over one third of the general population had been exposed to SARS-CoV-2 in Mexico by December 2020 [ 6 , 7 ]. While prevalence depends on the moment of estimation, as well as on duration of immunity, it is expected to increase after each epidemiological wave.…”
Section: Introductionmentioning
confidence: 99%
“…According to that study, the seroprevalence for the northwest region (including Baja California) was 40.7%. 25 A study conducted among people who inject drugs in Tijuana during the same period as this study found that 36.5% tested SARS-CoV-2 positive. 3 Our seroprevalence results are, therefore, consistent with the review by Hayward et al who concluded that migrants have been disproportionately affected during the pandemic, when compared with the native-born or general population and should be targeted in prevention efforts.…”
Section: Discussionmentioning
confidence: 59%
“…By the end of 2020, previous studies in Campeche, Mexico and before the vaccination program started, showed the seroprevalences were between 10%–20% in the unvaccinated population [ 11 ]. In the present work 42 % (60/141) corresponded to unvaccinated subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, in Mexico there have been few publications in base-population to capture enough epidemiological data; two works at national level describe the transmission dynamics during 2020, indicating a national prevalence of 24–33 % by the end 2020 [ 10 , 11 ]. Two more other studies were carried out in cities located in the northern and southeastern part of Mexico during the same year of 2020; the seroprevalence was 27 % and 21 %, respectively by the end of the same year [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%